Perkembangan Desa Wisata Sawarna Tahun 2002–2020 - Solihah; Rustama, Agus; Ribawati, Eko (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to determine the development of the Sawarna Tourism Village in 2002–2020. The method used is the historical method, including heuristics, source criticism, interpretation, and historiography. The results showed that Sawarna Village is located in Bayah District, Lebak Banten Regency, Sawarna Tourism Village has various potentials including nature tourism (maritime tourism and caves), cultural tourism (cultural arts, arts and crafts, pilgrimage tourism, Bubu Sawarna tourism and Sawarna harvest festival), and artificial tours (Sawarna best festival, Sawarna beach festival). Sawarna Tourism Village was initiated by Erwin Komarasukma since 1990, in 1999 Sawarna's potential was further explored, until 2002 Sawarna was made a tourist guided village. In 2014 there was a Village Head's decision regarding the inauguration of the Sawarna Tourism Village (Dwiwarna). The development of Sawarna Village cannot be separated from the role of the government and the people of Sawarna Tourism Village. Sawarna Tourism Village has social and cultural impacts, social impacts including (population structure, livelihood transformation, family modernization and value transformation), cultural impacts include giving birth to community or groups that concentrate on developing their traditional culture, one of which is the Dwiwarna studio in the Sawarna tourist village. Keywords: Development, Tourism Village, Sawarna